Use of Live Biopreservatives and Bacteriophages to Enhance the Safety of Meat Products - Rodriguez-Marca, Cristina; Domenech-Coca, Cristina; Nakamura, Miho; Ortega-Olive, Nadia; Puigbo, Pere (MDPI AG, 2025)
Critical health considerations for both raw and processed meats include addressing bacterial spoilage and ensuring safety. Nitrites and nitrates are widely used in the meat industry to enhance color and flavor and extend shelf life. However, health concerns linked to their use make reducing nitrites and nitrates in meat production a significant challenge with potential benefits for both the food industry and consumer health. This challenge has been addressed with the use of biopreservatives, i.e., substances extracted from natural sources or produced by fermentation that can enhance food quality and safety. In this article, we assess the use of live biopreservatives (LBs), defined here as microorganisms that produce antimicrobial substances that can be used to preserve and extend the shelf life of food. Moreover, the potential synergistic effects of LBs with bacteriophages and biodegradable food packaging for meat is also explored. This innovative combination offers a comprehensive approach to meat preservation, enhancing both microbial control and sustainability. Overall, the inclusion of LBs extends the shelf life of meat products through bacteriostatic mechanisms, whereas bacteriophages offer direct (lytic) action against pathogens. Enhancing meat preservation and safety with mixed microbe-mediated strategies requires deeper empirical and theoretical insights and further revision of laws and ethical considerations.